Integrating Generative AI into Project-based ESP Learning: A Fashion Design Case in Chinese Vocational Education - Shiqi Wang; Tumennast Erdenebold (Journal of Exploration of Vocational Education, 2025)
This study applies the Craftsmanship unit from New Orientation English 1 to implement an AI-enhanced project-based learning (PBL) model for English for Specific Purposes (ESP) in Chinese vocational colleges. Targeting fashion design majors, the project links English learning with professional skills and cultural heritage promotion through a simulated Fashion Week, where students present their garments with live English commentary. Multimodal generative AI tools (including language models, image generators, and AI-based audio platforms) were integrated across a five-phase PBL cycle consisting of initiation, skill-building, production, presentation, and reflection to scaffold vocabulary development, oral communication, design visualization, and presentation rehearsal. Findings suggest that AI-supported PBL improved linguistic accuracy, professional relevance, and learner engagement, while AI usage logs helped mitigate over-reliance. By integrating ESP learning, vocational skill development, and cultural communication within authentic industry-like contexts, this approach demonstrates practical value for fashion education and offers potential for broader adoption in fields such as art, tourism, and hospitality